2015
DOI: 10.21909/sp.2015.03.694
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Drive for Muscularity Among Adolescent Males

Abstract: Abstract:The aim of the current study was to explore body satisfaction, peer pressure and body shame as predictors of drive for muscularity among adolescent males. A total of 213 adolescent males completed the questionnaires assessing body satisfaction, peer pressure, body shame and drive for muscularity. The results indicated that drive for muscularity was predicted by body shame and body satisfaction. Participants' BMI, age, and experienced level of peer pressure did not play a role as significant predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…In one study, expressed dissatisfaction significantly predicted drive for muscularity in male college students (Pritchard et al, 2011). Similarly, body dissatisfaction was found to be a significant predictor for drive for muscularity in adolescent boys (Mustapic et al, 2015). More specifically, Tylka (2011) found that muscle dissatisfaction was related to muscularity-related behavior (e.g., exercising) while dissatisfaction with body fat was related to disordered eating behavior in undergraduate men.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In one study, expressed dissatisfaction significantly predicted drive for muscularity in male college students (Pritchard et al, 2011). Similarly, body dissatisfaction was found to be a significant predictor for drive for muscularity in adolescent boys (Mustapic et al, 2015). More specifically, Tylka (2011) found that muscle dissatisfaction was related to muscularity-related behavior (e.g., exercising) while dissatisfaction with body fat was related to disordered eating behavior in undergraduate men.…”
Section: Introductionmentioning
confidence: 92%
“…Investigating MD symptoms in a sample of male bodybuilders, Boyda and Shevlin (2011) found a relation between childhood victimization, such as verbal, physical, and social bullying and MD. It was argued, that regular critique and emotional victimization by parents (Lamanna et al, 2010) and peers (Boyda and Shevlin, 2011) may lead to body image distortion and higher degrees of body dissatisfaction which, according to other studies (Pritchard et al, 2011; Mustapic et al, 2015), are related to drive for muscularity. More generally, it was found that negative appearance-based comments were associated with higher body dissatisfaction and higher driver for muscularity (Nowell and Ricciardelli, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian oleh An (2017) pada sampel remaja pengguna media sosial menunjukkan bahwa pada perempuan, kecenderungan pengawasan tubuh akan menimbulkan ketidakpuasan bentuk tubuh, sedangkan pada laki-laki kecenderungan menginternalisasi standar budaya yang akan menimbulkan ketidakpuasan bentuk tubuh pada individu. Terdapat pula penelitian yang menemukan hubungan positif antara dimensi pengawasan tubuh serta dimensi internalisasi pandangan budaya dan rasa malu terhadap tubuh dengan ketidakpuasan bentuk tubuh pada sampel remaja, remaja pengguna internet, remaja pengguna media sosial, dan dewasa awal (Butkowski et al, 2019;Cassone et al, 2016;Knauss et al, 2008;Melioli et al, 2015;Mustapic et al, 2015;Sun, 2018). Dari hasilhasil penelitian sebelumnya, diketahui bahwa pengawasan tubuh serta internalisasi pandangan budaya dan rasa malu terhadap tubuh memiliki hubungan yang positif dengan ketidakpuasan bentuk tubuh.…”
Section: Pendahuluanunclassified
“…A variety of studies found negative relations of DfM with body image-related factors such as body shame and body dissatisfaction (Mustapic et al, 2015) or socio-cultural factors such as internalization of male body ideals (Daniel and Bridges, 2010) and social body comparisons (Stratton et al, 2015). Furthermore, negative associations with psychological factors or symptoms were found, such as anabolic steroid misuse (Litt and Dodge, 2008), lower self-esteem (Murray et al, 2013), depression (Edwards et al, 2014), and ultimately muscle dysmorphia (MD, Robert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%